Reduced high-intensity-running rate in college women`s soccer when games are separated by 42 hours - McCormack, W. P.; Hoffman, J. R.; Pruna, G. J.; Scanlon, T. C.; Bohner, J. D.; Townsend, J. R.; Jajtner, A. R.; Stout, J. R.; Fragala, M. S.; Fukuda, D. H. (International Journal of Sports Physiology and Performance, 2015)
Purpose: During the competitive soccer season, women`s intercollegiate matches are typically played on Friday evenings and Sunday afternoons. The efficacy of a 42-h recovery period is not well understood. This investigation was conducted to determine performance differences between Friday and Sunday matches during a competitive season. Methods: Ten NCAA Division I female soccer players (20.5 ± 1.0 y, 166.6 ± 5.1 cm, 61.1 ± 5.8 kg) were monitored with 10-Hz GPS devices across 8 weekends with matches played on Friday evenings and Sunday afternoons. The players were outside backs, midfielders, and forwards. All players had to participate in a minimum of 45 min/match to be included in the study. Average minutes played, total distance covered, total distance of high-intensity running (HIR) (defined as running at a velocity equal to or exceeding 3.61 m/s for longer than 1 s), the number of HIR efforts, and the number of sprints were calculated for each match. Data for Friday vs Sunday matches were averaged and then compared using dependent t tests. Results: No differences were seen in minutes played, distance rate, or number of sprints between Friday and Sunday matches. A significant (P = .017) decrease in rate of HIR between Friday (25.37 ± 7.22 m/min) and Sunday matches (22.90 ± 5.70 m/min) was seen. In addition, there was a trend toward a difference (P = .073) in the number of efforts of HIR between Friday (138.41 ± 36.43) and Sunday (126.92 ± 31.31). Conclusions: NCAA Division I female soccer players cover less distance of HIR in games played less than 48 h after another game. This could be due to various factors such as dehydration, glycogen depletion, or muscle damage.